Decolonization at Contemporary Culture ( Study of Social Sciences and Humanities) - Khamid, Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
Decolonization is an opportunity for countries that have been colonized as well as the state of Indonesia. Colonization, which has been going on in Indonesia for hundreds of years, has bequeathed and transformed ethical values and norms to colonized communities. Colonialism gave birth to nationalism that inspired colonized communities to commit acts of decolonization in an attempt to move on from the various cultures left behind by the colonial. Decolonization was widely done towards the beginning of independence and post-independence of Indonesia. But decolonization after more than 77 years since Indonesia became independent, the spirit slowly disappeared. Global culture has taken over the spirit of decolonization and replaced it with neocolonial culture in the contemporary culture